Effect of size, toasting degree and time of extraction on the volatile composition of a model wine solution treated with american oak chips - Boronat, Núria Ferré (2018)
Mestrado Vinifera Euromaster - Instituto Superior de Agronomia - UL / Universitá degli Studi di Torino